KEBIJAKAN PENANGGULANGAN PENURUNAN ANGKA STUNTING DI INDONESIA - Primanto, Aji; Puspitasari, Linda (CV. Lafadz Jaya, 2024)
Stunting is a chronic nutritional problem in children under five years of age characterized by being shorter than their peers. Children who suffer from stunting will be more vulnerable to disease and as adults are at risk of developing degenerative diseases. The impact of stunting is not only in terms of health but also affects the level of children's intelligence. Children are the assets of the nation in the future. It can be imagined, what will be the condition of Indonesia's human resources in the future if many Indonesian children are currently suffering from stunting. It is certain that this nation will not be able to compete with other nations in facing global challenges. To prevent this, the government launched an integrated stunting prevention intervention program that involves cross-ministries and institutions. There are 2 (two) main targets that must be met immediately, namely 1) the availability of Specific Intervention services with 9 (nine) indicators, and 2) the availability of Sensitive Intervention services with 11 (eleven) indicators.